RECONSTRUCTING SCIENCE TEACHING MATERIAL CONTAINING NATURE OF ‎SCIENCE ON THE TOPIC OF MATERIAL PARTICLES AND CHARACTERISTICS ‎ - maharani savitri; Ahmad Mudzakir (EDUSAINS, 2017)
This study was conducted to reconstruct teaching material of particles of matter using context of characteristics of material. It refers to the Model of Educational Reconstruction (MER). The purpose of this study was to obtain a pre-conception of learners and scientist’s perspective to the concept of particles of matter, material characteristics, and relations between them; determine the design of teaching materials based onviews of nature of science; and find out an expert assessment of the design of teaching materials. The research data obtained in the form of the transcript of an interview 10 students of class VIII, text analysis results, the results of the validation indicators and the learning objectives of cognitive and affective aspects, validation results of the analysis of the concept, validation results of teaching materialsdesign and test results readability. Design of teaching material produced is (a) developed based on reflection from pre-conception of learners and the perspective of scientists; (b) adjusted to the cognitive level of learners (accessible); (3) developed by inserting aspects of nature of science (NOS); (4) using a sequence of teaching and learning of Science and Technology Literacy (STL) by adopting a learning phase ChemieimKontext (ChiK). The results of the validation of teaching materials to obtain an average value of CVI 0,9935. This suggests teaching materials produced it feasible used for junior high students. Keywords:characteristic of matter; Model of Educational Reconstruction (MER); the nature of science;the  particles of matter; and teaching materialThis study was conducted to reconstruct teaching material of particles of matter using context of characteristics of material. It refers to the Model of Educational Reconstruction (MER). The purpose of this study was to obtain a pre-conception of learners and scientist’s perspective to the concept of particles of matter, material characteristics, and relations between them; determine the design of teaching materials based onviews of nature of science; and find out an expert assessment of the design of teaching materials. The research data obtained in the form of the transcript of an interview 10 students of class VIII, text analysis results, the results of the validation indicators and the learning objectives of cognitive and affective aspects, validation results of the analysis of the concept, validation results of teaching materialsdesign and test results readability. Design of teaching material produced is (a) developed based on reflection from pre-conception of learners and the perspective of scientists; (b) adjusted to the cognitive level of learners (accessible); (3) developed by inserting aspects of nature of science (NOS); (4) using a sequence of teaching and learning of Science and Technology Literacy (STL) by adopting a learning phase ChemieimKontext (ChiK). The results of the validation of teaching materials to obtain an average value of CVI 0,9935. This suggests teaching materials produced it feasible used for junior high students.